2017
DOI: 10.18017/iuitfd.348847
|View full text |Cite
|
Sign up to set email alerts
|

Mannose Binding Lectin (Mbl) Gene Polymorphisms and Their Relations With Clinical Features in Patients With Familial Mediterranean Fever (Fmf)

Abstract: ÖZET Amaç: Kompleman aktivasyonunun lektin yolağında rol oynayan ve doğal immün sistemin bir parçası olan mannoz bağlayıcı lektin (MBL), çeşitli patojenlerin mannan gruplarının uyarısı ile aktive olur. MBL genindeki bazı polimorfizmler (örn. kodon 52, kodon 54 polimorfizmleri) MBL'nin serum düzeylerinde değişikliklere yol açarak, infeksiyon hastalıklarına yatkınlığa neden olabildiği gibi, bazı otoimmün ve inflamatuvar hastalıkların patogenezine de katkıda bulunabilir. Bu çalışmada, ailesel Akdeniz ateşi (AAA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…19 Genetic polymorphisms in the MBL2 gene can interfere with the protein assembly, causing low serum levels of MBL, impairing its biological function, enhancing susceptibility to infectious diseases, and mediating various autoimmune as well as inflammatory disorders. 18,20,21 This study aimed to investigate MBL serum levels and (gly54asp -rs1800450) polymorphism in RAS patients to evaluate whether MBL can be used as a future therapeutic target in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…19 Genetic polymorphisms in the MBL2 gene can interfere with the protein assembly, causing low serum levels of MBL, impairing its biological function, enhancing susceptibility to infectious diseases, and mediating various autoimmune as well as inflammatory disorders. 18,20,21 This study aimed to investigate MBL serum levels and (gly54asp -rs1800450) polymorphism in RAS patients to evaluate whether MBL can be used as a future therapeutic target in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, frequent respiratory tract infections cannot be explained by low serum MBL levels. A study with adult patients with FMF having MBL gene R52CC>T and G54DG>A polymorphisms showed that the frequency was not different from healthy individuals [ 29 ].…”
Section: Discussionmentioning
confidence: 99%